Domingo na praia para além do baculejo: transatlanticidade, divisão racial na cidade / do espaço e juventudes negras na Praia do Poço da Draga em Fortaleza (CE) - Freitas, Paulo Henrique Ferreira de (2023)
This research identifies, embodies and presents sketches of cartographies, narratives and photographs of the urban space under the banks of the peripheral beaches of Fortaleza (CE) with a focus on Praia do Poço da Draga. It starts from a physical and existential understanding of the Black Atlantic interpreted by researchers who focus on the construction of black-African diasporas to address experiences constructed and modified by the black presence in coastal cities, specifically here, Fortaleza. The approach to the research field was carried out through participant observation, interviews and through collaborations with young black artists in the areas of music, poetry and visual arts in Fortaleza, which highlights representations of sociability, relationships of belonging and transgressions of young black people in the city and in urban spaces. The approach carried out through an intense presence in the field, interviews and collaborative participation during the research highlights the representations of sociability, relationships of belonging and transgressions of young black people in the city of Fortaleza. It is possible in this ethnography to make visible a debate about black youth in the plural contexts of their daily experiences in relation to the right to the city and more specifically, the right to the beach and leisure, art and culture, not limited to interpretations about the genocide of black youth as strict concept to rights violations in police approaches, extermination and mass incarceration practiced by the Brazilian State against young black people, but filling gaps and silences around racism and its strategies for maintaining power in large Brazilian cities